2009
DOI: 10.3354/ame01311
|View full text |Cite
|
Sign up to set email alerts
|

Emission spectroscopy and kinetic fluorometry studies of phototrophic microbial communities along a salinity gradient in solar saltern evaporation ponds of Eilat, Israel

Abstract: The planktonic and benthic microbial communities in 8 hypersaline evaporation ponds of the Israel Salt Company in Eilat, Israel, with salinities ranging from 58 to 329 g l -1 (total dissolved salt), were studied using fluorescence emission spectroscopy and kinetic fluorometry. With increasing salinity, the anoxygenic phototrophic bacteria (containing bacteriochlorophyll a, bchl a) formed a significant and increasing fraction of the planktonic phototrophic biomass. While the bchl a/chl a molar ratio was 0.01 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 22 publications
3
7
0
Order By: Relevance
“…We assume that it may be able of facultative anoxygenic photosynthesis with sulfide as electron donor. This would be in accordance with the findings of Prášil et al (2009) who have detected photosynthetic activities corresponding to cyanobacteria in these deep sediment layers in Eilat. The ability to switch between oxygenic and anoxygenic photosynthesis has been previously reported by Cohen et al (1977) from Oscillatoria limnetica, and is known from some other cyanobacteria as well (Garlick et al, 1977).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We assume that it may be able of facultative anoxygenic photosynthesis with sulfide as electron donor. This would be in accordance with the findings of Prášil et al (2009) who have detected photosynthetic activities corresponding to cyanobacteria in these deep sediment layers in Eilat. The ability to switch between oxygenic and anoxygenic photosynthesis has been previously reported by Cohen et al (1977) from Oscillatoria limnetica, and is known from some other cyanobacteria as well (Garlick et al, 1977).…”
Section: Discussionsupporting
confidence: 93%
“…The dominance of diatoms in the sediment is unique and has not been yet reported from other similar salterns. The recent study of Prášil et al (2009) demonstrated that photosynthesis of these diatoms is active even in deeper layers of the sediment. The results of other studies indicated that diatoms accounted only for low proportions of cells throughout the salinity gradient (Nübel et al, 2000;Jonkers et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The distribution pattern of photosynthetic microorganisms in the mats observed in the salterns of Eilat (Oren et al 1995, Prá$il et al 2009) was similar to those reported for other mats found in hypersaline environments, e.g. Salins-de-Giraud, France (Caumette et al 1994) and Guerrero Negro on the Pacific coast of Baja California, Mexico (Rothschild et al 1994).…”
Section: Microbial Community Of the Gypsum Crustssupporting
confidence: 85%
“…Low temperature (77K) emission spectra of intact cells sampled from water and ice. Samples were gently filtered on GF/F filters, cooled to liquid nitrogen temperature and illuminated by monochromatic light while recording the emission spectrum as described previously (Prášil et al, 2009). For this study, samples were excited with monochromatic light at 425 nm which is mostly absorbed by chlorophylls (left column) or at 534 nm which is mostly absorbed by carotenoids and phycobilins (right column).…”
Section: Freshwater Ice As Habitat?mentioning
confidence: 99%